(untitled) (Bangladesh Journal of Physics, 2025)
Alloy ribbons with the composition Fe73.5-xCrxCu1Nb3Si13.5B9 (where x = 1, 5, 10, 12.5, 17.5) are produced using a rapid quenching technique and subsequently annealed at various temperatures. The development of a homogeneous, ultra-fine grain structure, and also confirmation of the Fe(Si) phase, are examined through X-ray diffraction analysis. As the temperature increases, the amorphous nature of the as-prepared ribbons begins to diminish due to the onset of crystallization nucleation. Differential Scanning Calorimetry (DSC) measurements clearly show that the crystallization temperature shifts to higher values with increasing heating rates and time. A strong correlation between the onset of crystallization and the volume fraction of the crystalline α-Fe(Si) phase is observed through differential thermal scanning calorimetry. Additionally, Field Emission Scanning Electron Microscopy (FESEM) is employed to capture micrographs at different annealing temperatures, reflecting variations in the Cr content. Bangladesh Journal of Physics, Vol. 29, Issue 1, pp. 13 – 24, June 2022